NEUROPHARMACOLOGICAL SCREENING, ANTI-STRESS ACTIVITY, AND TOXICITY STUDIES OF STANDARDIZED EXTRACT OF THE SEEDS OF CELASTRUS PANICULATUS WILLD - SINGH, SWATI; UPADHYAY, ASHUTOSH; KUMAR SIRBAIYA, ANUP (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Celastrus paniculatus Willd, family Celastraceae is an important medicinal plant distributed all over India. Due to the presence of antioxidative polyphenols in C. paniculatus Willd have received much attention for health-promoting properties by scavenging the free radicals, the purpose of this study is to understand neuropharmacological, anti-stress activity, and toxicity studies of standardized seeds extract of “C. paniculatus Willd. Methods: The sun dried C. paniculatus Willd seeds were collected and extracted with ethanol by maceration. Then, the ethanolic extract was subjected to phytochemical screening. The acute toxicity of the ethanolic extract of C. paniculatus was observed as per the Organization for Economic Co-operation and Development guideline no. 423. Neuropharmacological and anti-stress effects were analyzed and evaluated by using physical stress models such as Swimming endurance test, Anoxic tolerance test, Tail suspension test (TST), and Elevated plus maze test. For this study, Swiss albino mice (20–30 g) were divided into five groups of six animals each. Distilled water administered as vehicle in control group and standard group received Withania somnifera (100 mg/kg) while C. paniculatus Willd ethanolic extract (100, 200, and 400 mg/kg) was given orally for 7 days. Results and Discussion: Change in immobility time in swim endurance, first clonic convulsion produced in anoxic tolerance test, immobility time in TST and open arms entry in elevated plus maze test was recorded as parameters. The ethanolic extracts of C. paniculatus Willd significantly reduces the immobility timing along with increases the swimming endurance time, and clonic convulsion timing in anoxic tolerance test in comparison of control group. In tail suspension significant decrease in immobility time and increased open arm entry in elevated plus maze were observed as compare to control group. Conclusion: C. paniculatus Willd has potential as a medicinal plant and it showed protective effect for the stress prevention as the alkaloids are present as main constituents.